Evidentiality in interaction - Nuckolls, Janis B.; Michael, Lev (Benjamins current topics, 2014)
This chapter describes two quotation strategies employed by speakers of Nanti, one involving grammaticalized quotatives and another involving complement-taking verbs of saying, and examines the consequences of the pragmatic differences between these strategies for two key questions in the study of evidentiality: first, the importance of degree of grammaticalization in delimiting 'evidentials'; and second, the importance of the analytical distinction between epistemic modal and 'source of information' evidential meanings. Nanti use of the two quotation strategies is specifically analyzed in the.